LAMA WAKTU PERENDAMAN BENIH MENGGUNAKAN ASAM SULFAT (H2SO4) TERHADAP DAYA KECAMBAH DAN PERTUMBUHAN SEMAI SAGA (Adenanthera pavonina L.) - Saila, Junita; Arlita, Tuti; ', M. Mardhiansyah (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
Diversityof tree speciescan be foundin the forest. One of diversity of tree species is Adenanthera pavonina L. Adenanthera pavonina L. used tree parts such as seed, leaves andwood. One of the seed used forcultivation. Germination of Adenanthera pavonina L. still thereobstacles which Adenanthera pavonina L. Seed has dormanty time. Skerification can be used by Sulfuric Acid (H2SO4). This research aims to find out seed immersion effect used H2SO4 andÂ  knowing better seed immersion time of germination Adenanthera pavonina L. This research compiled in Completely Randomize Design (CRD) with3treatments and 3 replications. The treatment inthis study wasa longtimeimmersionfor 10 minutes, 20minutes and30minutes. Datawere analyzedbyanalysis of varianceusingPortableSAS.9.1.3. Subsequentlyfollowed bymultiplerange testDNMRTlevel of 5%. Research resultsobtainedisa longtimeimmersioneffect onseed germinationsaga. The length of timeit is best toseedimmersionfor 30minuteswith germinationof48.66%, germinationpercentage ofthe seeds of 32,66%andthe seedsgerminateaverageof 6.75days. Keywords : Adenanthera pavonina L., dormancy, germination, immersion.